Impact of low quality power (Power quality)
Shows the effects of quality-related disturbances on equipment, systems, and human beings. Effects on equipment include sensitive electronic equipment, transformers, rotating machines, capacitors, and cables. System impacts include a variety of problems associated with poor power quality: instrumentation errors, false tripping, flicker annoyance, resonances, and economic penalties. Considers also the negative impact of power quality disturbances on communication systems, electric shock, and electromagnetic fields.